Atrogin‐1 Increases Smooth Muscle Contractility Through Myocardin Degradation. Issue 4 (21st July 2016) - Singh, Pavneet; Li, Dong; Gui, Yu; Zheng, Xi‐Long
Abstract : Atrogin‐1, an E3 ligase present in skeletal, cardiac and smooth muscle, down‐regulates myocardin protein during skeletal muscle differentiation. Myocardin, the master regulator of smooth muscle cell (SMC) differentiation, induces expression of smooth muscle marker genes through its association with serum response factor (SRF), which binds to the CArG box in the promoter. Myocardin undergoes ubiquitylation and proteasomal degradation. Evidence suggests that proteasomal degradation of myocardin is critical for myocardin to exert its transcriptional activity, but there is no report about the E3 ligase responsible for myocardin ubiquitylation and subsequent transactivation. Here, we showed that overexpression of atrogin‐1 increased contractility of cultured SMCs and mouse aortic tissues in organ culture. Overexpression of dominant‐negative myocardin attenuated the increase in SMC contractility induced by atrogin‐1. Atrogin‐1 overexpression increased expression of the SM contractile markers while downregulated expression of myocardin protein but not mRNA. Atrogin‐1 also ubiquitylated myocardin for proteasomal degradation in vascular SMCs. Deletion studies showed that atrogin‐1 directly interacted with myocardin through its amino acids 284–345. Immunostaining studies showed nuclear localization of atrogin‐1, myocardin, and the Rpt6 subunit of the 26S proteasome. Atrogin‐1 overexpression not only resulted in degradation of myocardin but also increased recruitment of RNA Polymerase II onto the promoters of myocardin target genes. In summary, our results have revealed the roles for atrogin‐1 in the regulation of smooth muscle contractility through enhancement of myocardin ubiquitylation/degradation and its transcriptional activity. J. Cell. Physiol. 232: 806–817, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Atrogin‐1 is an E3 ligase present in skeletal, cardiac and smooth muscle. Our study has shown that atrogin‐1 down‐regulates myocardin protein in human vascular smooth muscle cells, but increases transcriptional activity of myocardin on its target genes.